Improving Chicken Responses to Glycoconjugate Vaccination Against Campylobacter jejuni - Nothaft, Harald; Perez-Muñoz, Maria Elisa; Yang, Tianfu; Murugan, Abarna V. M.; Miller, Michelle; Kolarich, Daniel; Plastow, Graham S.; Walter, Jens; Szymanski, Christine M. (Frontiers in Microbiology, 2021)
Campylobacter jejuni is a common cause of diarrheal disease worldwide. Human infection typically occurs through the ingestion of contaminated poultry products. We previously demonstrated that an attenuated Escherichia coli live vaccine strain expressing the C. jejuni N-glycan on its surface reduced the Campylobacter load in more than 50% of vaccinated leghorn and broiler birds to undetectable levels (responder birds), whereas the remainder of the animals were still colonized (non-responders). To understand the underlying mechanism, we conducted 3 vaccination and challenge studies using 135 broiler birds and found a similar responder/non responder effect. Subsequent genome-wide association studies (GWAS), analyses of bird sex and levels of vaccine induced IgY-responses did not correlate with the responder versus non-responder phenotype. In contrast, antibodies isolated from responder birds displayed a higher Campylobacter-opsonophagocytic activity when compared to antisera from non-responder birds. No differences in the N-glycome of the sera could be detected, although minor changes in IgY glycosylation warrant further investigation. As reported before, the composition of the microbiota, particularly levels of OTU classified as Clostridium spp., Ruminococcaceae and Lachnospiraceae are associated with the response. Transplantation of the cecal microbiota of responder birds into new birds in combination with vaccination resulted in further increases in vaccine-induced antigen-specific IgY responses when compared to birds that did not receive microbiota transplants. Our work suggests that the IgY effector function and microbiota contribute to the efficacy of the E. coli live vaccine, information that could form the basis for the development of improved vaccines targeted at the elimination of C. jejuni from poultry.